PENDANAAN PENDIDIKAN ISLAM: Sebuah Tinjauan Historis - Muh. Idris (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2008)
In its history, the development of Islamic education closely related to the financing. The financing sources of this institu-tion are not only from government, but also from itself supporting earning mainly from students or other shapes of educational economic activities. The donation institution is one of these economic activity that can decrease the ignorance and retardation by education and development of sciences. That donation institution plays important role in developing Islamic education in Indonesia.